PERAN PAJAK RESTORAN TERHADAP PENERIMAAN DAERAH ADMINISTRASI JAKARTA TIMUR - Dede Suleman (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2019)
one of the local taxes is restaurant tax. in this research, it will give a big picture of contributing restaurant tax to Jakarta Timuel's original revenue. Regional taxes are divided into three types, taxes levied by local governments, taxes collected based on national regulations, but income tariffs made by local governments. Restaurant tax is a service provided by payment, a service provided by a restaurant called service includes the sale of food and / or drinks consumed by the buyer, whether consumed at the service place or elsewhere. The subject of restaurant tax is an individual or entity that makes payments to restaurants or restaurants, cafes, bars and the like, while taxpayers are individuals or entities that run restaurants. The restaurant tax rate set is 10%. restaurant tax revenue increases every year and can exceed the target set only in 2014 restaurant tax revenue is only 82%. restaurant tax contribution increases every year for East Jakarta administrative city tax revenues, which has a significant influence in 2014 amounting to 46.78% and 2015 at 50.19% and 2016 at 55.69%